The spirit catches you and you fall down ebook A hmong child, her american doctors, and the collision of two cultures. - Fadiman, Anne (1998)
Winner of the National Book Critics Circle Award for Nonfiction The Spirit Catches You and You Fall Down explores the clash between a small county hospital in California and a refugee family from Laos over the care of Lia Lee, a Hmong child diagnosed with severe epilepsy. Lia's parents and her doctors both wanted what was best for Lia, but the lack of understanding between them led to tragedy. Winner of the National Book Critics Circle Award for Nonfiction, the Los Angeles Times Book Prize for Current Interest, and the Salon Book Award, Anne Fadiman's compassionate account of this cultural impasse is literary journalism at its finest. ______ Lia Lee 1982-2012 Lia Lee died on August 31, 2012. She was thirty years old and had been in a vegetative state since the age of four. Until the day of her death, her family cared for her lovingly at home.